2005
DOI: 10.1159/000084053
|View full text |Cite
|
Sign up to set email alerts
|

Cheyne-Stokes Respiration in Congestive Heart Failure: Continuous Positive Airway Pressure of 5–8 cm H<sub>2</sub>O for 1 Year in Five Cases

Abstract: Five adult patients with congestive heart failure (CHF) due to dilated cardiomyopathy complicated by Cheyne-Stokes respiration/central sleep apnea (CSR/CSA) were treated with continuous positive airway pressure (CPAP) with an initial pressure of 5 cm H2O. Four patients were followed up for 12 months with CPAP of 5 cm H2O. The rest, a 93-year-old patient, was followed up for 30 months, and the CPAP was reset at 8 cm H2O due to worsened cardiac function after 6 months and it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…These results were approved in further studies [17, 18]; moreover, the authors found a dose-related positive effect using different pressures (5 and 10 cm H 2 O). It was shown that CPAP at a level of 5–8 cm H 2 O was associated with an improvement of cardiac function and symptoms in 5 patients with heart failure and Cheyne-Stokes respiration [19]. In patients with normal left ventricular filling pressures and in normal controls, CPAP affected a decrease in cardiac index.…”
Section: Discussionmentioning
confidence: 99%
“…These results were approved in further studies [17, 18]; moreover, the authors found a dose-related positive effect using different pressures (5 and 10 cm H 2 O). It was shown that CPAP at a level of 5–8 cm H 2 O was associated with an improvement of cardiac function and symptoms in 5 patients with heart failure and Cheyne-Stokes respiration [19]. In patients with normal left ventricular filling pressures and in normal controls, CPAP affected a decrease in cardiac index.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the CPAP was adjusted to 5-8 cmH2O, according to the method described by Yasuma (9,10), which is lower than the conventional optimal CPAP pressure of 10-12.5 cmH2O for patients with CHF (11). In contrast, Genovese et al demonstrated that, in pigs with pacinginduced CHF, the cardiac output and left ventricular ejection fraction were enhanced with the use of CPAP at a pressure of 5 cmH2O (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, we applied this strategy to 5 consecutive heart failure patients with central sleep apnea for 6 h per night for 1 year with success. 8 Any of the aforementioned clinical investigations lacked the power to conclude with certainty that nightly oxygen, Bi-PAP or CPAP is effective in improving the morbidity or mortality of patients with congestive heart failure. 1,2,6,8 The interaction among sleep, respiration and circulation is a newly developing field in cardiology (the so-called new cardiovascular frontier 9 ), as indicated by the fact that only 17 years have passed since one of the earliest studies dealing with Cheyne-Stokes respiration in congestive heart failure appeared in this Journal.…”
Section: To the Editormentioning
confidence: 99%